Awareness and use of family planning information by women in Abeokuta South Local Government Area of Ogun State, Nigeria (2018)
Family planning is a comprehensive medical and social practice which enables individuals to determine easily the number and spacing of their children and to select the means of its achievement. The information on the knowledge of family planning services is referred to as family planning in-formation (FPI). Failure to use FPI often results in problems such as unwanted pregnancy, unsafe abortions, infants and maternal deaths, rapid population growth and sexually transmitted infections; among others. To avoid these problems, awareness of FPI is paramount but rather it appears to be low. The government, medical practitioners and the media are really bothered about the seeming apathy and unenthusiastic awareness of FPI by women. It is against this background that this research examined the aware-ness and use of family planning information by women in Abeokuta South Local Government Area of Ogun State, Nigeria. Descriptive survey design was adopted for the study; simple random and accidental sampling techniques were used to select the sample size of 250 women of childbearing age (15-49 years). Questionnaire was the chief re-search instrument and data was analysed using descriptive statistics of frequency counts and percentages for the four research questions. Findings showed that some of the respondents were using family planning methods while many were not because of fear of side effects, lack of awareness, and partner’s disagreement; among others. Awareness of FPI was found to be average but the level of use was low. The study therefore recommended that awareness of family planning information must be encouraged, quality of education and health-care services should be improved, and adequate funding should be ensured for procurement of required tools and equipment.